2015
DOI: 10.4172/2161-1017.1000193
|View full text |Cite
|
Sign up to set email alerts
|

Leptin, Insulin and Lipid Profiles in Obese Subjects with and without Metabolic Syndrome in the Region of Cap-Bon: Tunisia

Abstract: Aims: To evaluate the effect of obesity associated or not with Metabolic Syndrome (MS) on leptinemia, insulinemia and lipid profile in subjects from the region of Cap-Bon in northeastern Tunisia. Methods: Ninety seven individuals were included in this study. Anthropometric parameters (Body Mass Index (BMI), Waist Circumference (WC) and Hip Circumference (HC), metabolic parameters (Total Cholesterol (TC), LDL-C, HDL-C, Non-Esterified Fatty Acids (NEFA), Triglycerides (TG), C˗Reactive Protein (CRP), glucose) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
(31 reference statements)
3
4
0
Order By: Relevance
“… 34 Genetic, geographic, study selection criteria and dietary pattern may also vary across populations studied. The high Median leptin levels in this study is somewhat similar to previous reports in Industrialized countries, 18 , 22 , 23 , 25 , 27 , 35 , 36 some African 24 , 26 and Nigerian studies. 16 , 31 , 32 It however, contrasts report of much lower leptin levels in some other geographical locations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“… 34 Genetic, geographic, study selection criteria and dietary pattern may also vary across populations studied. The high Median leptin levels in this study is somewhat similar to previous reports in Industrialized countries, 18 , 22 , 23 , 25 , 27 , 35 , 36 some African 24 , 26 and Nigerian studies. 16 , 31 , 32 It however, contrasts report of much lower leptin levels in some other geographical locations.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous reports from most African, 16 , 24 , 28 , 30–33 American 14 , 17 , 18 , 21 , 27 , 34 and studies from other continents. 22 , 23 , 25 , 26 , 35 , 37 There was however, variations in Median leptin concentrations across populations, ethnicities and geographical locations. Most African-American, even population-based studies, 17 , 18 , 27 , 28 , 34 , 36 reported higher leptin levels in blacks than whites, attributed to higher subcutaneous tissue than visceral adipose tissue, as more leptin is produced from the latter than the former.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this study, we did not find any significant correlation between HOMA-IR with CSLR and FLI. These results are consistent with those observed by Fadoua et al [45]. Theoretically, leptin exerts an insulin-sensitizing and glucose-lowering effect in the peripheral tissues, which can be observed by looking at the HOMA-IR value.…”
Section: Circulating Soluble Leptin Receptor and Free Leptin Index Insupporting
confidence: 93%
“…Theoretically, leptin exerts an insulin-sensitizing and glucose-lowering effect in the peripheral tissues, which can be observed by looking at the HOMA-IR value. However, leptin and insulin resistance in obese individuals may make these effects less distinct; therefore, we did not find any significant correlation between HOMA-IR with CSLR and FLI [45,46]. These results need to be confirmed further as other studies revealed contrary results.…”
Section: Circulating Soluble Leptin Receptor and Free Leptin Index Inmentioning
confidence: 53%